Dilema Pembangunan Pariwisata Berkelanjutan Di Kawasan Tiga Gili Kabupaten Lombok Utara - Sutanto, Himawan (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
Regional tourism development has many benefits for the region development. The high demand for the tourism industry could threat the sustainability of tourism. With a descriptive approach, this study aimed to analysis of sustainable tourism dilemma. The results show there is a dilemma such as on environmental-social-economic environment, socio-economics is still going on and not inevitable because human nature is homoeconomicus. Utilization of the environment as a tourist commodities bring positive effects for the economy of society, but caused by the high rates of inequality and income distribution between the Gili people and non-Gili people. The rapid flow of tourists in the 3 Gili make lifestyle surrounding communities turned into hedonic and party culture that is incompatible with local culture. Disparity income which can trigger jealousy. Fishery production is going to decline given some rules on no-take areas in the Water Park Zone 3 Gili. The balanced on 3-D sustainability triangle (Environmental Capacity, Social Capacity and Economic Capacity) must be maintain.